2015
DOI: 10.1056/nejmoa1504869
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, Primary Aldosteronism, and AdrenalCTNNB1Mutations

Abstract: SUMMARYRecent discoveries of somatic mutations permit the recognition of subtypes of aldosteroneproducing adenomas with distinct clinical presentations and pathological features. Here we describe three women with hyperaldosteronism, two who presented in pregnancy and one who presented after menopause. Their aldosterone-producing adenomas harbored activating mutations of CTNNB1, encoding β-catenin in the Wnt cell-differentiation pathway, and expressed LHCGR and GNRHR, encoding gonadal receptors, at levels that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 25 publications
(34 reference statements)
4
82
2
1
Order By: Relevance
“…Berthon et al (13) recently reported Wnt/b-catenin activation in a majority of APA, related to the downregulation of a negative regulator of this pathway, named SFRP2 -this Familial adenomatous polyposis downregulation seems to be due to a high methylation of SFRP2 promoter (13). Another recent publication identified CTNNB1 mutations -encoding the b-catenin -in Conn adenomas in pregnant women (14). The relationship between the calcium signaling activation and the Wnt/b-catenin pathway remains to be elucidated.…”
Section: Methodsmentioning
confidence: 99%
“…Berthon et al (13) recently reported Wnt/b-catenin activation in a majority of APA, related to the downregulation of a negative regulator of this pathway, named SFRP2 -this Familial adenomatous polyposis downregulation seems to be due to a high methylation of SFRP2 promoter (13). Another recent publication identified CTNNB1 mutations -encoding the b-catenin -in Conn adenomas in pregnant women (14). The relationship between the calcium signaling activation and the Wnt/b-catenin pathway remains to be elucidated.…”
Section: Methodsmentioning
confidence: 99%
“…Teo and coworkers reported the case of three women with PA due to an APA with somatic CTNN1B mutations (p.Ser33Cys, pSer45Phe and p.Gly34Arg), two diagnosed during pregnancy and the third after menopause (Teo et al 2015). Their APA expressed high levels of luteinizing hormone-chorionic gonadotropin receptor (LHCGR) and gonadotropin-releasing hormone receptor (GNRHR), suggesting that pregnancy may reveal underlying PA (Teo et al 2015).…”
Section: Mutations Affecting β-Catenin Activationmentioning
confidence: 99%
“…In addition, these mutation cases have distinct char- acteristics, including male dominance, increased plasma aldosterone concentration, and lower potassium concentration, compared with cases without these mutations (Beuschlein et al 2013). In addition, Teo et al (2015) reported three cases of APA with activating mutations in CTNNB1 encoding β-catenin, associated with aberrant β-catenin accumulation in the Wnt cell-differentiation pathway and overexpression of luteinizing hormone/choriogonadotropin receptor (LHCGR) and gonadotropin-releasing hormone receptor (GnRHR). Subsequently, CTNNB1 mutations have been reported in 5.1% of APA cases, and APA tissues with CTNNB1 mutations were demonstrated to have a significantly higher CYP11B2 mRNA expression level compared with those with KCNJ5 mutations (Åkerström et al 2016).…”
Section: Somatic Mutations In Aldosterone-driver Genes and Cyp11b2 Exmentioning
confidence: 99%